Sunda Language Reservation in Cianjur on The Age to Learn - Wati Kurniawati; Emzir Emzir; Sabarti Akhadiah (JETL (Journal of Education, Teaching and Learning), 2018)
This study aims to gain an understanding of Sundanese language reservation in Kota Cianjur at the compulsory school age. The observations focused on the domains of Sundanese use that included the family and education sphere. The problem in this research is how the reservation of Sundanese language is viewed from the point of choice of language with the domain of its use? In this research used qualitative approach with ethnography method. The ethnographic research procedure in this study is 1) define sub focus, 2) observation and interview, 3) collect data, 4) make notes, 5), analyze data, and 6) make ethnographic reports. The research findings show that the form of speech is a statement, a question, a greeting, a thank-you note, a formula phrase, a solicitation, a request to do something, an apology, an order, and an agreement. Based on the Sundanese language reservation category in Cinajur city at the compulsory education age in the family realm is maintained (85--100%). The participants of Sundanese speech have a positive loyalty and attitude towards the language. Meanwhile, the education sphere is less maintained (51-74%). In the realm of education, there can be a shift in language because it is poorly maintained and the said participants have no balance in lending languages.